Students of the Dream : Resegregation in a Southern City - Yow, Ruth Carbonette (Harvard University Press, 2017)
Documenting the half-century-long drama of integration in Marietta, Georgia, Students of the Dream grapples with the past, present, and future of integrated schooling in America. Once the most desegregated region in the country, the South is now facing rapid resegregation of its schools. The widespread failure to address resegregation--at the level of local, state, and national education policy--endangers the destinies of millions of the South's, and the nation's, most vulnerable children. This book poses school resegregation as the fundamental social justice battle of our time. It offers historical context as well as contemporary findings to reveal the origins and evolution of a new integration era, which in some ways draws on, and in other ways rejects, the legacy of Brown v. Board of Education. Students of the Dream describes generations of student "dreamers": from those who made real the dream of integrated schooling in the years after the 1954 Brown v. Board decision to those who fight for educational justice today.--